성인에서 시행된 선천 상사근마비의 수술 결과 - 차유완; 김대현 (Daihan angwa haghoi jabji, 2023)
목적: 선천 상사근마비의 수술적 교정이 성인 이후에 시행된 환자들의 수술 결과에 대해 알아보고자 하였다. 대상과 방법: 선천 상사근마비의 수술적 교정이 18세 이후에 시행된 환자 35명의 의무기록을 후향적으로 분석하였다. 수술 후 최종경과 관찰 시 잔여상사시가 4 prism diopters (PD) 이하면 성공군, 잔여상사시가 5 PD 이상이거나 과교정되면 실패군으로 분류하였다. 두 군 간 임상 양상을 비교하여 수술 결과에 영향을 미치는 인자에 대해 알아보았고 최종 관찰 시 머리기울임 및 복시 등의 주관적증상 소실 여부도 확인하였다. 결과: 전체 환자 35명 중 24명(68.6%)이 성공군, 11명(31.4%)이 실패군으로 분류되었다. 두 군 간의 임상 양상 중 술 전 수직사시각이실패군에서 성공군보다 더 크게 나타났다(23.1 PD vs. 15.2 PD, p<0.05). 술 전 머리기울임이 있던 31명의 환자 중 29명(93.5%)에서머리기울임이 소실되었고 복시를 호소하던 19명의 환자에서는 과교정된 1명을 제외하고 모두 복시가 소실되었다. 결론: 선천 상사근마비수술이 성인 이후에 시행된 경우 술 전 수직사시각이 수술 결과에 영향을 미칠 수 있을 것으로 생각된다. 머리기울임 및 복시는 대부분 교정되어 주관적 증상 소실 예후는 좋았다. Purpose: To investigate the outcomes of patients who underwent surgical correction of congenital superior oblique muscle paralysis in adulthood. Methods: We retrospectively analyzed the medical records of 35 patients who underwent surgical correction of congenital superior oblique muscle paralysis after the age of 18 years. At the final follow-up, success was defined as residual hypertropia < 4 prism diopters (PD), whereas failure was defined as residual hypertropia ≥ 5 PD or overcorrection. Clinical features were compared between the success and failure groups to identify factors affecting the surgical outcome. At the final follow-up, the resolution of symptoms, such as head tilt and diplopia, was also recorded. Results: Of the 35 patients, 24 (68.6%) and 11 (31.4%) were classified into the success and failure groups, respectively. Preoperative vertical deviation was larger in the failure group compared to the success group (23.1 vs. 15.2 PD, respectively; p < 0.05). Of the 31 patients with preoperative head tilt, head tilt resolved in 29 (93.5%). Of the 19 patients with diplopia, it resolved in all except 1 who was overcorrected. Conclusions: The preoperative vertical angle of the superior oblique muscle may affect the outcome of surgery performed in adulthood for correcting congenital superior oblique paralysis. Head tilt, diplopia, and subjective symptoms are typically resolved postoperatively. KCI Citation Count: 0